Calculation and experimental measurement of paramagnetic NMR parameters of phenolic oximate Cu(ii) complexes. Issue 76 (4th September 2017) - Dawson, Daniel M.; Ke, Zhipeng; Mack, Frederick M.; Doyle, Rachel A.; Bignami, Giulia P. M.; Smellie, Iain A.; Bühl, Michael; Ashbrook, Sharon E.
Abstract : Unusual 1 H and 13 C NMR shifts for paramagnetic bisoximato copper(ii ) complexes are understood by combining DFT calculations and multidimensional experiments. Abstract : We present a strategy for predicting the unusual 1 H and 13 C shifts in NMR spectra of paramagnetic bisoximato copper(ii ) complexes using DFT. We demonstrate good agreement with experimental measurements, although 1 H– 13 C correlation spectra show that a combined experimental and theoretical approach remains necessary for full assignment.